2023
DOI: 10.52728/ijjm.v4i1.619
|View full text |Cite
|
Sign up to set email alerts
|

The The Impact of Working Environment on Employee Loyalties with Job Satisfaction as an Intervening Variable

Abstract: In this dynamic era, maintaining loyal and qualified human resources is a step to increase company productivity in order to achieve set goals. Many factors affect employee satisfaction, one of which is job satisfaction. Maintaining employee loyalty by increasing the level of job satisfaction is done by creating a conducive and positive work environment. The work environment includes the physical environment, psychological environment, and social environment. This study aims to determine the effect of the work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
1
3
0
6
Order By: Relevance
“…In addition, organizational management must encourage employee initiative and creativity. According to (Andarsari and Setiadi 2023) Cleanliness is part of the work environment. It may not have the potential to motivate directly, but if ignored, it can cause dissatisfaction.…”
Section: Percentage Outmentioning
confidence: 99%
“…In addition, organizational management must encourage employee initiative and creativity. According to (Andarsari and Setiadi 2023) Cleanliness is part of the work environment. It may not have the potential to motivate directly, but if ignored, it can cause dissatisfaction.…”
Section: Percentage Outmentioning
confidence: 99%
“…The results showed that job satisfaction have a positive and significant effect on employee loyalty. (Andarsari & Setiadi, 2023) also explained that the work environment affects employee job satisfaction, which significantly contributes to enhancing employee loyalty to the company. Furthermore, the research conducted by (He et al, 2022) indicated that paradoxical leadership has a significant positive effect on employee loyalty, with job satisfaction serving as a partial mediator between paradoxical leadership and employee loyalty.…”
Section: Figure 1 Diagram Of Employee Distribution According To Job F...mentioning
confidence: 99%
“…One of these factors is the relationship between internal communication, job satisfaction, employee loyalty and service quality. Research has shown that internal communication satisfaction plays an important role in improving employee engagement and overall organizational performance (Andarsari & Setiadi, 2023). In addition, a positive work environment, including physical, psychological and social aspects, can increase job satisfaction and employee loyalty (Dharmawan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%